Older Workers and the Adoption of New Technologies - Jenny Meyer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
For the first time data of German ICT and knowledge intensive service providers are used to analyze the relation between the age structure of the workforce and the probability of adopting new technologies. The results show that firms with a higher share of younger employees are more likely to adopt new technologies and the older the workforce the less likely is the adoption of new technologies. Furthermore the results exhibit that the age structure of the workforce should be accompanied by appropriate workplace organization. A part of the firms which enhanced teamwork or flattened their hierarchies are actually more likely to adopt new technologies and software when they have a higher share of older employees whereas they are less likely to introduce new technologies if they have a higher share of younger employees.
Older version: http://hdl.handle.net/10419/24621
Keywords: O31; J14; 330; age structure of the workforce; adoption of new technologies; ICT intensive services; Computergestütztes Verfahren; Innovationsdiffusion; Arbeitskräfte; Lebensalter; Ältere Arbeitskräfte; Organisationsstruktur; Schätzung; Deutschland